Contribuições do Projovem Campo – Saberes da terra na formação de jovens agricultoras/es familiares no Bico do Papagaio - Alves, Márcia Flausino Vieira (Universidade Federal do Tocantins, 2023)
Education as a right of all runs through the paths of the contributions of Education of the Field. In this perspective, the present study has the general objective of analyzing the contributions of the Programa ProJovem Campo – Saberes da Terra to farmation young family farmers in the micro region Bico do Papagaio, Tocantins. To this end, we opted for the qualitative approach, because as a research exercise, it does not present itself as a rigidly structured proposal for the generation and interpretation of data, rather it allows imagination and creativity to lead researchers to propose works that explore new approaches, new perceptions and new horizons. In classifying the techniques used, this study uses bibliographic and documentary research. This technique collects its data samples from primary sources, such as documents written or not, belonging to public archives, private archives of institutions and households and statistical sources. From descriptive statistics, it uses position measures that serve to characterize what is “typical” in a particular group studied from the presentation of data through tables and graphs. The ProJovem Campo – Saberes da Terra (2005-2012) served a total of 774 students at Bico do Papagaio in Tocantins during its term, promoting social and professional training based on the Program's proposals. The data indicate the achievement of a Program that was developed for young family farmers, which, through the Family Farming and Sustainability course, promoted social and professional qualification with prospects for contributing to the development of work, income generation and permanence of young people in communities in the Bico do Papagaio micro region.